Undocumented migrants and the hegemonic ideology of the system of territorial states : a critical analysis of ideological contention in Irish Christians' moral imagination - Jackson, Damian (Irish School of Ecumenics, 2013)
States respond punitively to those who cross their borders without authorisation. Consequently the human rights of undocumented migrants, often including the right to life itself, are systemically denied them. Every year, about 800 people die trying to enter the European Union, with little enough protest against such unjust and violent occurrences. The questions behind this research seek to probe how such a morally flimsy system persists with little critique, and how it influences moral reasoning so that it is the undocumented migrants who are typically held responsible for their own predicament, and portrayed as a threat in popular discourse.
Keywords: Religions, Theology & Ecumenics Ph.D.; Ph.D. Trinity College Dublin